Insecticidal activity of a proteinaceous α-glycosidase inhibitor isolated from an endophytic Aspergillus awamori and its biosafety evaluation. (December 2021) - Singh, Bahaderjeet; Dhaliwal, Ram Singh; Kumar, Parvesh; Singh, Amanpreet
Abstract: Agriculture Sector has been affected largely by biotic and abiotic stresses. Among biotic challenges faced by agriculture is the damage caused by insect pests. Insecticides are being widely used for rapid and effective management of insect pests. Despite of their usefulness, the excessive use of insecticides poses potential risks to food safety and environment. To reduce the usage of chemicals, biological control of insect pest can be effective alternative of insecticides for sustainable agriculture. The present study aims to evaluate the insecticidal potential of a protein obtained from an endophytic Aspergillus awamori against insect pest Spodoptera litura (Fab). Variable concentrations of the inhibitor induced high larval mortality ranging from 16.67 to 53%. Larval, pupal and total developmental period of S. litura increased significantly at higher concentrations. The LC50 value of the inhibitor was determined to be 34.34 μg/ml. A significant decrease in adult emergence was recorded at all the concentrations with maximum inhibitory effect at 30 μg/ml where only 65.94% adults emerged as compared to 100.00% in control. The in vivo effect of the inhibitor on gut α-amylase and α-glucosidase was also studied. The activity of α-amylase and α-glucosidase was suppressed to 33.84% and 38.13%, respectively after 72 h at highest concentration of 40 μg/ml. The biosafety evaluation of the extract revealed that the strain is ochratoxin negative and noncytotoxic which supports the above findings that it could be used as biocontrol agent. Highlights: 1) The fungi Aspergillus awamorii can be exploited for the production of α-glycosidase inhibitors. 2) The proteinaceous extract exhibits In vivo α-glycosidase inhibitory activity against enzymes of Spodoptera litura. 3) The biosafety evaluation suggested that the extract is ochratoxin negative and noncytotoxic to humans.